License to Sell : The Effect of Business Registration Reform on Entrepreneurial Activity in Mexico - Bruhn, Miriam (World Bank, Washington, DC, 2012)
This paper studies the effect of business registration regulation on economic activity using micro-level data. The identification strategy exploits the fact that a recent business registration reform in Mexico was introduced in different municipalities at different points in time. Using panel data from the Mexican employment survey, I find that the reform increased the number of registered businesses by 5 percent in eligible industries. This increase was due to former wage earners opening businesses. Former unregistered business owners were not more likely to register their business after the reform. Moreover, employment in eligible industries went up by 2.8 percent, and people who were previously unemployed or out of the labor force were more likely to work as wage earners after the reform. Finally, the results imply that the competition from new entrants lowered prices by 0.6 percent and decreased the income of incumbent businesses by 3.2 percent.